IMPLEMENTATION THE CONCEPT OF KNOWLEDGE AND METHODOLOGY ACCORDING TO IBNU ABDU AL-BAR ON ISLAMIC CONTEMPORARY EDUCATIONAL INSTITUTION - Syafii, Bakrun (Sekolah Tinggi Ilmu Ushuluddin (STIU) Darul Hikmah, 2021)
Science according to Ibn Abd Al-Bar is the knowledge that is believed to be true, clearly known from various sides, and does not change in essence. According to him, science is classified into two parts, first, dhoruri science which can be known axiomatically, and second, acquired-based science which is conducted through mind analysis (such as scientific science) and textual-based (such as religious sciences). Both are grouped into three levels: religious science, scientific science, skill science. This paper aims to describe the integral and comprehensive concept of Ibn Abd Al-Bar and its implementation in contemporary Islamic educational institutions, by synergizing science and religion. The research method used in this paper is the inductive method and the analytical method. The inductive method was used to collect information related to Ibn Abd Al-Bar's concept of education, to collect verses of the Qur'an and the Prophet's Hadith related to education in Ibn Abd Al-Bar's concept, and to collect information related to the contemporary Islamic education system, particularly in Indonesia. The analytical method is used to analyze the implementation of the educational concept according to Ibn Abd Al-Bar into the contemporary Islamic education system. This research resulted in several important conclusions. First: The purpose of education in the concept of Ibn Abd Al-Bar is to nurture obedient students to worship Allah. This goal is implemented in the recitation, purification, and education programs. Second: The educational curriculum according to Ibn Abd Al-bar must have three criteria; confidence, clarity, and determination. This curriculum is implemented based on the classification of science, various sciences, and its rules to study the sciences. Third: The educational method in the concept of Ibn Abd Al-Bar can be implemented in various methods; methods of listening, understanding, memorizing, practicing, and teaching. Fourth: Educational Evaluation should be measured by practice indicators, obedience indicators, and submission indicators.